Metabolic patterns of JWH-210, RCS-4, and THC in pig urine elucidated using LC-HR-MS/MS: do they reflect patterns in humans? - Schäfer, Nadine; Meyer, Markus Robert (Drug testing and analysis, 2017)
The knowledge of pharmacokinetic (PK) properties of synthetic cannabinoids (SCs) is important for interpretation of analytical results found for example in intoxicated individuals. In the absence of human data from controlled studies, animal models elucidating SC PK have to be established. Pigs providing large biofluid sample volumes were tested for prediction of human PK data. In this context, the metabolic fate of two model SCs, namely 4‐ethylnaphthalen‐1‐yl‐(1‐pentylindol‐3‐yl)methanone (JWH‐210) and 2‐(4‐methoxyphenyl)‐1‐(1‐pentyl‐indol‐3‐yl)methanone (RCS‐4), was elucidated in addition to Δ9‐tetrahydrocannabinol (THC). After intravenous administration of the compounds, hourly collected pig urine was analyzed by liquid chromatography‐high resolution mass spectrometry. The following pathways were observed: for JWH‐210, hydroxylation at the ethyl side chain or pentyl chain and combinations of them followed by glucuronidation; for RCS‐4, hydroxylation at the methoxyphenyl moiety or pentyl chain followed by glucuronidation as well as O‐demethylation followed by glucuronidation or sulfation; for THC, THC glucuronidation, 11‐hydroxylation, followed by carboxylation and glucuronidation. For both SCs, parent compounds could not be detected in urine in contrast to THC. These results were consistent with those obtained from human hepatocyte and/or human case studies. Urinary markers for the consumption of JWH‐210 were the glucuronide of the N‐hydroxypentyl metabolite (detectable for 3–4 h) and of RCS‐4 the glucuronides of the N‐hydroxypentyl, hydroxy‐methoxyphenyl (detectable for at least 6 h), and the O‐demethyl‐hydroxy metabolites (detectable for 4 h).